The Manoe Pucok Tradition in Wedding Celebrations in West Aceh: An Ethnographic Study in Johan Pahlawan District: Tradisi Manoe Pucok dalam Perayaan Pernikahan di Aceh Barat: Studi Etnografi di Kecamatan Johan Pahlawan - Riyan Firdaus; Manan, Abdul; Saprijal, Saprijal; Ruhamah, Ruhamah; Wahyuni, Hamdina (Indonesian Journal of Islamic History and Culture, 2026)
The manoe pucok tradition is one of the customary practices that plays an important role in the wedding procession of the Meulaboh community in West Aceh Regency and is still practiced to this day. This tradition not only serves as a complement to the wedding ceremony but also symbolizes respect for cultural values ​​passed down from generation to generation by ancestors. This article aims to describe and analyze the implementation of the manoe pucok, radat of manoe pucot performed, and the values contained in manoe pucot tradition at wedding ceremony in Drien Rampak Village, Johan Pahlawan district West Aceh. The research method used is a qualitative method with an ethnographic approach. Data were collected through direct observation of the wedding procession, in-depth interviews with traditional leaders, customary practitioners, and local community members, and were strengthened by documentation as supporting data. The results of the study indicate that the manoe pucok tradition is carried out through several customary stages that have specific rules and symbolic meanings and are adhered by the supporting community. It contains radat to symbolically cleanse (manoe) the bride and groom before entering their new lives. This procession involves sprinkling water with young leaves (pucok) and is accompanied by ritual elements and traditional arts. This tradition contains religious values ​​that reflect prayers, hopes, and requests for blessings for the married couple's household life; social values ​​that play a role in strengthening kinship ties and reinforcing community solidarity and togetherness; cultural values ​​that affirm the local identity of the community; and historical values ​​as a form of preserving customary heritage that has existed over a long period of time. This tradition function not only as a customary ritual in marriage but also as a medium for preserving local culture that reflects the identity of the local community.